Removal of Cd from Aqueous Solution by Na[sup.+]-Modified Pisha Sandstone - Wang, Xia; Cui, Yongxing; Peng, Qi; Fan, Chenbin; Zhang, Zhiqin; Zhang, Xingchang (Journal of chemistry, 2020)
Heavy metals have caused serious environmental issues, which are enriched during open-cast coal mining. It is urgent to develop sustainable remediation materials to protect and restore the contaminated soil and aquifers in mining areas. The feasibility of applying Pisha sandstone (PS) and Na[sup.+]-modified Pisha sandstone (Na-PS) for adsorption of heavy metals was evaluated. Na-PS exhibited maximum Cd(II) and Cu(II) removal rates of 65.9% and 99.8%, respectively, exceeding the corresponding values for PS (8.2% and 1.3%, respectively) in 1×10[sup.-3]M solution. Efficient heavy metals adsorption occurred in the pH range 5.0-6.0. The adsorption of Cu(II) and Cd(II) on PS and Na-PS was characterized by kinetic models and adsorption isotherms and was well represented by pseudo-second-order kinetics (R[sup.2]>0.99) and the Langmuir and Freundlich isotherm models. The values of the thermodynamic parameters indicated that the interactions were spontaneous endothermic reactions. Binary solutions adsorption isotherms indicated that the linearity of the adsorption amount and initial concentration of Cu(II) and Cd(II) was better in certain ranges and the adsorbents were selective towards Cu(II) rather than Cd(II). Therefore, PSs can be used as excellent adsorbents for Cu(II) and Cd(II) remediation from contaminated surface water.